Activated Clotting Time and Haemostatic Complications in Patients Receiving ECMO Support: A Systematic Review - Daniel Schwaiger; Lukas Schausberger; Benedikt Treml; Dragana Jadzic; Nicole Innerhofer; Christoph Oberleitner; Zoran Bukumirić; Igor Spurnić; Sasa Rajsic (Journal of Cardiovascular Development and Disease)
Background: Extracorporeal membrane oxygenation (ECMO) requires systemic anticoagulation to prevent clotting, typically using unfractionated heparin (UFH). However, anticoagulation carries a bleeding risk, necessitating monitoring. Activated clotting time (ACT) is a commonly used monitoring tool for UFH anticoagulation. However, systematized evidence linking ACT monitoring with haemostatic complications (bleeding and thrombosis) is missing. Methods: A systematic review (Scopus and PubMed, up to 13 July 2024) including studies reporting on the patients receiving ECMO support with UFH anticoagulation monitored using ACT was performed. Results: A total of 3536 publications were identified, of which 30 (2379 patients) were included in the final review. Thirteen studies found no significant association between ACT values and haemorrhage, while four studies suggested a relationship between elevated ACT levels and bleeding events. Eight studies demonstrated no association between ACT values and the occurrence of thrombosis. Major bleeding was most common (49%, 13 studies with 501 events), while the pooled rate of thrombosis was 25% (16 studies with 309 events) and in-hospital mortality was 51% (17 studies, 693/1390 patients). Conclusions: Despite advancements in ECMO, the optimal approach for anticoagulation monitoring remains undefined. Most studies in this review did not establish a significant relationship between ACT levels and haemostatic complications. Based on the current evidence, ACT does not appear to be a reliable tool for monitoring anticoagulation in patients receiving ECMO, and alternative methods should be considered.